Exercise for reducing fear of falling in older people living in the community - Kendrick, Denise; Kumar, Arun; Carpenter, Hannah; Rixt Zijlstra, G.A.; Skelton, Dawn A.; Cooke, Juliette R.; Stevens, Zoe; Belcher, Carolyn; Haworth, Deborah; Gawler, Sheena J.; Gage, Heather; Masud, Tahir; et al. (Wiley, 2014)
Background: Fear of falling is common in older people and associated with serious physical and psychosocial consequences. Exercise (planned, structured, repetitive and purposive physical activity aimed at improving physical fitness) may reduce fear of falling by improving strength, gait, balance and mood, and reducing the occurrence of falls.